Toll‐like receptor 3 expression and function in childhood idiopathic nephrotic syndrome. (30th September 2015) - Jamin, A.; Dehoux, L.; Dossier, C.; Fila, M.; Heming, N.; Monteiro, R. C.; Deschênes, G.
Summary: The efficacy of steroids and immunosuppressive treatments in idiopathic nephrotic syndrome (INS) hints at the implication of immune cells in the pathophysiology of the disease. Toll‐like receptor (TLR) dysfunctions are involved in many kidney diseases of immune origin, but remain little described in INS. We investigated the expression and function of TLRs in peripheral blood mononuclear cells (PBMC) of INS children, including 28 in relapse, 23 in remission and 40 controls. No child had any sign of infection, but a higher Epstein–Barr virus viral load was measured in the PBMC of relapsing patients. TLR‐3 expression was increased in B cells only during INS remission. There was a negative correlation between proteinuria and TLR‐3 expression in total and the main subsets of PBMC from INS patients. The expression of TLR‐8 was also increased in both CD4 + T cells and B cells in INS remission. There was a negative correlation between proteinuria and TLR‐8 expression in total PBMC, CD4 + T cells and B cells of INS patients. Nevertheless, TLR‐3 and TLR‐8 expression was normalized in all PBMC subsets in an additional group of 15 INS patients in remission with B cell repletion after rituximab therapy. Paradoxically, interferon (IFN) regulatory factor 3 transactivation was increased in PBMC of all INS patients. In‐vitro secretion of IFN‐α and interleukin 6 were increased spontaneously in PBMC of INS remission patients, whereas PBMC from all INS patients displayed an impaired IFN‐α secretion after TLR‐3 stimulation. Thus, TLR‐3 pathway dysfunctions may be closely involved in INS pathogenesis.